Efficacy of 0.1 % Sodium Hyaluronate versus 0,5 % Carboxymethylcellulose in Dry Eye Disease : A Meta-Analysis: Poster Presentation - Observational Study - General practitioner - ALDILA SAVITRI; FITRIAN HANIF (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Dry eye is a disorder that involves either insufficient tear production or excessive tear evaporation. Artificial tears are the main treatment for dry eye disease. Sodium Hyaluronate (AH) and Carboxymethylcellulose (CMC) are the two most frequently prescribed and used. To analyze the efficacy of 0,1% sodium hyaluronate compared with 0,5% carboxymethylcellulose toward the symptom score, tear break up time, corneal stain fluorescein in dry eye through a meta-analysis. Methods : A systematic search was performed using Medline and Cochrane database up to December 2022. Review was performed according to the PRISMA Statement. The eligible studies were RCTs which comparing Sodium hyaluronate with Carboxymethylcellulose. Results : From 88 retrieved articles, 6 trials involving total 373 patients were included. The median follow-up period of the studies was 6 weeks. Sodium hyaluronate significantly increases tear break up time compared to Carboxymethylcellulose (Mean Difference (MD): 0.46, 95%CI [0.09-0.84], p=0.01, I2=76%), and significantly decrease corneal stain fluorescein (MD: -0.54, 95%CI [-0.86-(-0.23)], p=0.0008, I2=88%). The analysis shows insignificantly decrease in subjective symptom scores (MD: -0.08, 95%CI [-0.40-0.23], p<0.60, I2= 79 %). Conclusion : In dry eye disease, 0,1% sodium hyaluronate significantly improves tear break up time and significantly decreasing corneal stain fluorescein, while insignificantly decrease subjective symptom scores.